RESEARCH AND EVALUATION EDUCATIONAL - Espinoza Fernández, Carlos (2014)
The meaning of educational research has been set for qualitative and experimental flows in recent years. On the other hand, two are distortions of conventional research have led to its failure: first, using a methodology of experimental designs and second, applying theories and alien to the process of teaching conceptual frameworks. This made it possible for educational research to restart their own way from her natural object: education. In this regard, it should be to differentiate between the professor who assesses and researcher who teaches. I.e. between the efficient teacher who teaches for the domain to Professor cognitive research who teaches from doubt, with attitude hermeneutic with attitude dialectical prompting methodical change of position and perspective which evaluates to find explanations to their mistakes and find change of positions. Assess is to investigate, for us this means that all educational research is an interpretation, is a qualitative evaluation of the experience which is capable of being rational, and produces new knowledge. The dictator of class teacher becomes an assayer’s proposals for education and demonstrable self-regulatory strategies in practice. Note if your operation is effective in the short or mediumterm through regulatory activities, the respective support and return current and future information will help to organize their inquiries and find reasons and justifications for his teaching activities.